Geological spatial plan toward groundwater resources in Kertek, Wonosobo Basin, Central Java, Indonesia - Lutfian Rusdi Daryono; Melania Seta Dhesty Wijayaningsih; Agus Hendratno; Mochamad Nukman; Eddy Hartantyo; Satoru Kawasaki (Brawijaya University, 2019)
Human activity affects both natural resources and spatial land use, including its utilization as sand mining sites. Sand mines, as a pillar of building construction, have been over excavated in certain areas, which has impacted the environment. In this research, the purpose of this study was to determine a spatial allocation of the mining designation area that will not damage the groundwater flow. Therefore, it is imperative for understanding the depth of groundwater at the study site, understanding the direction of groundwater flow, and the impact of mining activities on groundwater based on the combination of geophysical and geological approaches to improve the current government policy. A geological-geophysics approach, vertical electrical sounding (VES), was followed at 12 different locations surrounding the Kertek District, which has a general geological formation of igneous volcanic rock sediment. The result of the geophysical measurements (possibilities) indicates the presence of shallow, medium, and deep groundwater aquifers, which tended to follow the slope direction to the south. This may be due to the unsaturated soil conditions as the geoelectrical measurements were taken at the beginning of the rainy season. Finally, the goals of this research were to integrate resources with spatial characteristics to allow proper resources management.